Factorize completely x^3 - 6x^2 + 11x - 6

  • Google+ icon
  • LinkedIn icon
  • 1965 views

Let f(x) = x^3 - 6x^2 + 11x - 6.

Try x = 1:   f(1) = 1 - 6 + 11 - 6 = 0

So x - 1 is a factot of f(x).

Try x = 2:   f(2) = 8 - 24 + 22 - 6 = 0

So x - 2 is a factot of f(x).

Try x = 3:  f(3) = 27 - 54 + 33 - 6 = 0

So x - 3 is a factot of f(x).

Thus         x^3 - 6x^2 + 11x - 6 = (x - 1)(x - 2)(x - 3)

Kai W. A Level Maths tutor, GCSE Maths tutor, A Level Further Mathema...

About the author

is an online A Level Maths tutor with MyTutor studying at Cambridge alumni University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok